Study the level of uric acid and its relationship with blood pressure disease. - Lina M. Z. Yosuf, M.Sc ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
The mechanisms involved in the shop uric acid and the fact that it may be a risk factor for diseases of pressure and near and intelligence, where the recent studies have linked the relationship between blood pressure and diabetes The current study of the findings of this hot relationship from December 2017 to March 2018 has been collected 200 samples from the hospital General Hospital in Maysan, Al-Majar Al-Kabeer Hospital / Maysan, as well as from the technical institute / architecture, Neuroscience Hospital / Baghdad and Al-Rumaytha General Hospital / Al-Muthanna. 80 samples of females were 80 male blood pressure patients, aged 25-65 years. Treatment Bone osteo-osteo-skeletal bone for most groups with uric acid values ​​The results of the present study showed a relationship between diastolic blood pressure and uric acid acid rate in females and males in the center of Maysan province and attrakur in Baghdad and females in Al-Rumaitha district and a relationship between systolic blood pressure and rate Acid uric acid in females in the center of the province of Maysan and females in the province of Rumaitha, while there remained nothing significant between random blood sugar and uric acid in all groups in the study.